2011
DOI: 10.1089/jpm.2010.0504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Comorbidity Burden on Health Care Utilization for Patients with Cancer Using Hospice

Abstract: Background: The treatment of patients with advanced cancer with multiple comorbid illnesses is complex. Although an increasing number of such patients are being referred to hospice, the comorbidity burden of this patient population is largely unknown but has implications for the complexity of care provided by hospices. This study reports the comorbidity burden in a national sample of hospice users with cancer and estimates the effect of higher comorbidity on health care use and site of death. Methods: Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 30 publications
6
44
1
Order By: Relevance
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 81%
“…In another previous study, almost 40% of the spouse caregivers reported depressive symptoms in a range that was likely to be clinically significant, a prevalence that was almost two-fold than their ill partners (Rittenberger et al, 2011). Previous studies have demonstrated that caregivers of patients with cancer have increased health problems and psychosocial stress (Bergen-Jackson et al, 2009;Kiely et al, 2010;Zhou et al, 2010;Bell et al, 2011;Gilbertson-White et al, 2011;Legler et al, 2011;Stevens et al, 2011). Therefore, in palliative care, care burden could have a bad impact on caregivers.…”
Section: Discussionmentioning
confidence: 97%
“…The process used to compile the IAHPC list of essential medicines in palliative care involved determination of common symptoms at the end of life and evaluation of medications used to treat those symptoms. 1 …”
Section: Discussionmentioning
confidence: 99%